Pengaruh Permodalan Bank terhadap Efisiensi Operasi dan Performa Intermediasi Perbankan - Jaysica Balen; Nesya Septry Tarigan; Anugrah Indah Siregar; Hamonangan Siallagan (Journal of Innovative and Creativity, 2026)
Banking plays an important role in the economy through its intermediary function, so capital adequacy and operational efficiency are key to maintaining stability and credit distribution. However, previous research findings on the relationship between capital adequacy and operational efficiency and intermediary performance are still diverse and require a more structured synthesis. This study aims to analyse the effect of bank capital on operational efficiency and banking intermediation performance. The method used is a literature study with a systematic literature review design. The research population consists of peer-reviewed scientific journal articles that discuss bank capital and its relationship with operational efficiency and/or banking intermediation. The sampling technique uses purposive sampling based on inclusion and exclusion criteria, resulting in a sample of 15 selected articles with active DOIs. The study location is focused on the Indonesian banking context with the support of international study findings as a comparison. The synthesis results show that capital adequacy is generally related to increased operational efficiency through strengthened risk management, governance, and cost control capacity, as well as strengthened intermediation capabilities through credit distribution resilience. However, the impact of capital is not always linear because unproductively managed capital has the potential to cause inefficiencies and an overly conservative attitude towards credit. The implication is that banks need to optimise capital utilisation for efficiency and productive credit distribution, while regulators need to ensure that capital policies promote stability and healthy intermediation.